2022
DOI: 10.1002/hed.27175
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic test accuracy of sentinel lymph node biopsy in squamous cell carcinoma of the oropharynx, larynx, and hypopharynx: A systematic review and meta‐analysis

Abstract: The aim of this meta‐analysis was to determine the diagnostic test accuracy of sentinel lymph node biopsy (SLNB) in patients with oropharyngeal, laryngeal, and hypopharyngeal squamous cell carcinoma (SCC). For this purpose, MEDLINE, EMBASE, and Web of Science were searched from inception to March 8, 2022. Included were studies evaluating diagnostic test accuracy of SLNB to identify cervical lymph node metastases with elective neck dissection or follow‐up as reference. A bivariate generalized linear mixed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…indicating that it could reliably identify patients who did not have lymph node metastases. The study suggested that SLNB could be a reliable tool in the planning of surgical treatment for OTSCC [ 24 , 27 , 28 , 29 ]. Similarly, Liu M. et al conducted a meta-analysis on the use of SLNB in the treatment of early OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…indicating that it could reliably identify patients who did not have lymph node metastases. The study suggested that SLNB could be a reliable tool in the planning of surgical treatment for OTSCC [ 24 , 27 , 28 , 29 ]. Similarly, Liu M. et al conducted a meta-analysis on the use of SLNB in the treatment of early OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Van den Bosch et al conducted a systematic review and meta‐analysis to determine the diagnostic performance of SLNB in laryngeal, oropharyngeal and hypopharyngeal carcinoma with [ 99m Tc]Tc‐nanocolloid injection under either topical or general anesthesia including 19 studies comprising 377 patients 24 . A pooled sensitivity of 0.93 (95% confidence interval (CI): 0.86–0.96) and pooled negative predictive value of 0.97 (95% CI: 0.94–0.98) was reported 24 . The pooled detection rate was 0.98 (95% CI: 0.94–1.0) and a mean number of 2.6 SLNs per patient were identified and surgically resected.…”
Section: Discussionmentioning
confidence: 99%
“…These side effects, and in particular dysphagia and xerostomia, are notoriously known to negatively and permanently affect quality of life [5] , [6] . The prevalence of occult metastases is approximately 30 % in patients with a clinically negative neck (based on physical examination and imaging) [7] . Therefore, the majority of patients will not benefit from ENI but do carry the burden of consequential radiation sequelae.…”
Section: Introduction/rationalementioning
confidence: 99%
“…To date, SLNB is not yet performed routinely in patients with larynx and pharynx cancer that are primarily treated with (C)RT. Recently, a systematic review and meta -analysis on the diagnostic test accuracy of SLNB in patients with SCC of the oropharynx (n = 162) and larynx/hypopharynx (n = 215) was published [7] . With pooled estimates of sensitivity and negative predictive value of 0.93 and 0.97 respectively, the diagnostic test accuracy was excellent.…”
Section: Introduction/rationalementioning
confidence: 99%